Cinephilia and history, or, The wind in the trees - Keathley, Christian (Indiana University Press, 2006)
This volume is, in part, a history of cinephilia, in part an attempt to recapture the spirit of cinephilia for the discipline of film studies, and, in part, an experiment in cinephilic writing.